2016
DOI: 10.1007/s41101-016-0010-2
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization of Methylene Blue Dye Using Sonocatalytic Followed by Photocatalytic Process

Abstract: The aim of the present investigation is to study the different methods to improve the photocatalytic decolorization using visible light photocatalyst. In this investigation, ZnO/ Bi 2 O 3 composite was prepared using hydrothermal method, and it is studied for the decolorization of methylene blue (MB) dye. Enhancement of decolorization has been done by ultrasonication followed by photocatalytic process. Considerable improvement was observed in sonocatalysis followed by photocatalytic process. Various operating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The decrease in CR dye uptake was mainly due to the limited amount of CR dye molecules in solution, and the CR dye concentration may be very dilute for this range of the AgNPs dosage. The results obtained agreed with previous work [20].…”
Section: Effect Of Phsupporting
confidence: 93%
“…The decrease in CR dye uptake was mainly due to the limited amount of CR dye molecules in solution, and the CR dye concentration may be very dilute for this range of the AgNPs dosage. The results obtained agreed with previous work [20].…”
Section: Effect Of Phsupporting
confidence: 93%
“…Once we confirmed that TFNs provided inertial cavitation in response to focused ultrasound, we next investigated the potential of the TFNs particles as sonophotocatalysts through degradation of MB and DPBF. Degradation of both MB and DBPF has already been investigated with photo- [24] , [25] and sonosensitizing agents [23] , [31] , [49] . MB was used as a model dye in our study as it belongs to a class of synthetic dyes that are non-biodegradable toxic runoff from the textile industry [24] .…”
Section: Resultsmentioning
confidence: 99%
“…Sonoluminescence from cavitation events in the fluid interacts with nearby photosensitizers to generate reactive oxygen species (ROS) [10] , [27] , [28] . Modifying the photosensitizers [23] , [28] , [29] , adding hydrogen peroxide (H 2 O 2 ), or including other stimuli (e.g., light) into the reaction solution have further enhanced ROS formation [30] , [31] . However, these methods lack spatiotemporal control of cavitation events; they rely on continuous wave ultrasound to nucleate and sustain cavitation.…”
Section: Introductionmentioning
confidence: 99%
“…The higher degradation rate was reported due to the formation of both HO • and SO 4 •− radical species. Balakumara et al [116] investigated the sonophototocatalyticdecolourization of MB in the presence of ZnO/Bi 2 O 3 synthesised using a hydrothermal method. An enhanced decolourization was observed in a sonophotocatalytic process performed under optimized experimental parameters.…”
Section: Sonophotocatalysismentioning
confidence: 99%